2004
DOI: 10.1590/s0037-86822004000700006
|View full text |Cite
|
Sign up to set email alerts
|

Hepatite C: prevalência e fatores de risco entre portadores do VIH/SIDA em Belém, Pará, na Amazônia brasileira

Abstract: RESUMO Este trabalho objetivou investigar a prevalência de infecção pelo vírus da hepatite C e identificar possíveis fatores de risco para sua transmissão, em 406 indivíduos portadores do vírus da imunodeficiência humana 16% (IC: 12,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]6Indivíduos portadores do vírus da imunodeficiência humana (VIH) estão freqüentemente co-infectados com outros vírus, incluindo-se os das hepatites. A possibilidade de associação do VIH com o vírus da hepatite C (VHC) em um … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 37 publications
0
7
0
4
Order By: Relevance
“…In Brazil, about 0.5% of the adult population is infected with HIV [1] and among those attending the public health services, 16% HIV-HCV co-infection rate had been reported in outpatient care centers [2], [3], 42% in HIV-HCV anonymous testing centers [4], and 54% for patients HIV infected in infectious diseases clinics [5].…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, about 0.5% of the adult population is infected with HIV [1] and among those attending the public health services, 16% HIV-HCV co-infection rate had been reported in outpatient care centers [2], [3], 42% in HIV-HCV anonymous testing centers [4], and 54% for patients HIV infected in infectious diseases clinics [5].…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, the prevalence of HCV is around 1% to 2% in the general population, but it ranges from 0.9% to 2.4% in the North region of the country [6,7] and it reaches more than 30% among injecting drug users [8]. Seroprevalence to HCV in the Pacui Island, Para, a small village within Cameta municipality, was 8.8% and RNA persistence was detected among 62.5% of the seroreactive subjects [9].…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, HCV prevalence in patients treated at health services in the Amazon was 16% (95%CI: 12.4-19.6) 14 . A study of HIV-infected individuals in the city of Santos showed a 36.2% co-infection rate (95%CI: 31.9-40.4), significantly higher among IDUs than non-IDUs (p < 0.001) 15 .…”
Section: Introductionmentioning
confidence: 99%